Analysis of the Impact of ChatGPT Usage in Direct Current Physics Material on Enhancing Students' Higher-Order Thinking Skills (HOTS) during the Merdeka Belajar - Zakaria Al Farizi; Sahlan Sahlan; Erwin Prasetyo; Nadya Fitriani; Elyakim Mau Laleng; Hamzarudin Hikma Tiar; Zaina Anwar (Universitas Lambung Mangkurat, 2024)
This study examines the influence of using ChatGPT to enhance students' higher-order thinking Skills (HOTS), particularly within the context of the